Sustainable Use of Antarctic Resources:Is It Compatible with the Status of Antarctica as a Natural Reserve? in Sustainable Development and International Law: the Way Forward (Working Group on Environmental Law) - VIGNI, PATRIZIA (European University Institute, 2007)
This article highlights the need for a specific regulation of the bioprospecting activities that are carried out in Antarctica in order to preserve the character of natural reserve of this area